Sepiolite/copper nanostructured compacts for healthcare and catalytic applications - S. Lopez-Esteban; R. Diaz; B. Cabal; A. Gil; E. Sotelo; J. Azuaje; J.F. Bartolome; J.S. Moya; C. Pecharroman (Materials & Design)
Sepiolite/copper nanostructured powders were successfully obtained by wet processing. Transmission electron microscopy studies showed the presence of Cu nanoparticles (average size about 20 nm), isolated and homogeneously distributed in the sepiolite fibers. Compacts with and without the addition of a low-melting-point glass were obtained by sintering at very low temperature (about 600 °C), either in air or in reducing atmosphere. The suitability of these compacts for catalysis and biocide applications was investigated. Regarding samples sintered in air, it has been shown for the first time that, at temperatures as low as 600 °C, the presence of Cu nanoparticles in the channels of the sepiolite structure promotes the formation of a copper magnesium silicate of clinoensteatite type, as well as the collapse of the sepiolite structure. Compacts sintered in reducing atmosphere present an excellent catalytic performance (95 % yield) in the synthesis of phenamic acid to prepare anti-inflammatory drugs. Moreover, the bactericidal activity against selected bacteria, such as Escherichia coli and antibiotic resistant strains (Methicillin-resistant Staphylococcus aureus), revealed strong bactericidal effects (>3 log reduction, 24 h). The procedure used in this work is readily scalable to low-cost industrial production, paving the way towards applications in critical fields like Medicine and Catalysis.